Poverty traps and growth in a model of endogenous time preference - Debajyoti Chakrabarty (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
We study the effect of endogenous time preference in a simple neo-classical model of growth. The variation of time preference causes the economy to have multiple steady states, some of which are similar to poverty traps. The stability properties of these steady states are analyzed. The results are interpreted in light of the growth experiences of developing economies. The model can explain why two economies that have identical production technologies and identical preferences may converge to different levels of income depending on initial conditions.
Keywords: D91; E21; C62; O40; 330; Intertemporal choice; Saving; Growth; Local stability; Poverty traps; Zeitpräferenz; Wachstumstheorie; Armut; Theorie